The Effectiveness of Android-Based E-Modul Discon (E-Modul Disroid) on Sound Material on Student Learning Outcomes - Azizah; Nurul Alifha; Zulnuraini; Sinta Satria Dewi Pendit (LPPM Universitas Tadulako, 2023)
This research aims to determine the effectiveness of the Android-based E-Modul Discon (E-Modul DISROID) in sound material on the learning outcomes of class V students at SD Inpres 6 Lolu. This research is a quantitative experimental research conducted on two groups, namely the experimental group and the control group. The research design used in this research is Quasi-Experimental with the form of a Control group Pre-test and Post-test design. The population in this study was the entire class V of SD Inpres 6 Lolu for the 2023/2024 academic year, totaling 54 students. The samples in this study were class Va as the control class and Vb as the experimental class. The instrument used is a test instrument, namely multiple choice questions whose validity and reliability have been tested. Data analysis used required tests, namely the normality test and homogeneity test as well as hypothesis testing using the Paired Sample t-test which was analyzed using SPSS For Windows 25. Based on the research results, it showed a significance value (2-tailed) of 0.000 < Î± value of 0.05. Because of the sig value. (2-tailed) 0.000 < 0.05 then accepting the Ha hypothesis and rejecting the Ho hypothesis, meaning that the use of the Android-based E-Module Discon (E-Module DISROID) in sound material is effectively used for student learning outcomes. Based on the results of hypothesis testing, it can be concluded that the use of the Android-based E-Modul Discon (E-Modul DISROID) in sound material is effective for the learning outcomes of class V students at SD Inpres 6 Lolu.